From Data to Awakening: A Seven-Level Typology for Transformative Research Aligned with the United Nations Sustainable Development Goals - Narsico, Peter G. (Future Science / FSH-PH Publications, 2026)
This paper presents a seven-level typology of research results (descriptive, interpretative, prescriptive, reflective, generative, transformative, meta-transformative) so that we can understand scholarly depth and impact. Fluid and interdependent, these levels guide research from observation to social change. Inspired by the ambitious goals of the United Nations Sustainable Development Goals, this typology suggests that research has to go beyond technical rigor to a higher ethical and human level. It is a way to question the level of evidence and conceptual depth that is necessary for researchers to bring data to life and to help them to view research as a pathway to creating a just, inclusive society for a sustainable planet. In sustainability, education, and health, research is transforming from something that is just to be right and just to be good as well as transformative. If one wants to frame inquiry as a recursive and sacred activity, then in this model it also creates the notion that research can reveal truths, empower communities and open up new opportunities in every field and culture and it is how research is to illuminate truths and to inspire communities and new possibilities in disciplines and cultures.